Potential Angiotensin‐Converting Enzyme Inhibitor—Epoetin Alfa Interaction in Patients Receiving Chronic Hemodialysis - Michael H. Schwenk; Abdul Q. Jumani; Carl R. Rosenberg; Josephine E. Kulogowski; Chaim Charytan; Bruce S. Spinowitz (Pharmacotherapy: The Journal of Human Pharmacology and Drug Therapy, 1998)
We compared epoetin alfa (EPO) dose requirements and hematocrit response in 17 patients receiving chronic hemodialysis at baseline and after 3 and 12 months of therapy with angiotensin‐converting enzyme (ACE) inhibitors (12 enalapril, 5 captopril). No acute processes were present (infection, hemorrhage, inflammation) at time of starting ACE inhibitor therapy. Mean (± SD) intravenous EPO dosages at zero, 3, and 12 months were 6012 ± 2575, 5800 ± 2026, and 5660 ± 2285 U 3 times/week (p=0.56), and mean differences were − 212 U for 0–3 months (95% CI −1310 to 886) and −713 U for 0–12 months (95% CI −2142 to 716). Mean ± SD hematocrits were 30.5 ± 3.9%, 31.6 ± 3.2%, and 34.2 ± 3.1% (p=0.01, zero vs 12 mo), and mean differences were 1.7% for 0–3 months (95% CI −1.41 to 4.81) and 3.85% for zero–12 months (95% CI 0.71–7). Our results indicate that ACE inhibitors do not increase EPO dose requirements or reduce hematocrits in these patients.